Composition for preparing fragile material, fragile material and anti-counterfeiting fragile label
By using a composition of resin, acrylic modified cellulose and other materials in a fragile anti-counterfeiting label, the problem of easy damage during production and use of the label is solved, and the initial tear resistance and fragility of the label is achieved, and excellent anti-counterfeiting performance and weather resistance are achieved.
Patent Information
- Application Number
- CN202411860594.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
AI Technical Summary
The existing fragile anti-counterfeiting laser printing labels are easily damaged during production and use, affecting their normal use, and are difficult to have both fragility and initial tear resistance.
Using a composition, including resin, acrylic modified cellulose, impact modifier, inorganic filler, thermoplastic elastomer and curing agent, the anti-counterfeiting label is formed through appropriate ratios, and combined with the synergistic effect of the mesh structure of the acrylic modified cellulose and the thermoplastic elastomer, the tear resistance and fragility of the label are improved.
It realizes tear resistance of anti-counterfeiting and fragile labels during production, transportation and use, avoids damage, and quickly decomposes into small fragments after being removed, and cannot be used intact again, achieving anti-counterfeiting purpose, and has excellent weather resistance, high temperature yellowing resistance and UV stability.
Smart Images

Figure CN119529516A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-counterfeiting materials, and in particular relates to a composition for preparing fragile materials, the fragile material and an anti-counterfeiting fragile label. Background Art
[0002] Fragile anti-counterfeiting laser printable labels have good fragility, so that they will break into pieces during the tearing process and cannot be preserved, thus achieving the purpose of anti-counterfeiting. However, their fragility also makes the labels easily damaged during production or normal use, affecting their normal use. Therefore, how to make this type of label have both fragile anti-counterfeiting performance and initial tear resistance is one of the problems that need to be solved urgently. Summary of the invention
[0003] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the objects of the present invention is to provide a composition for preparing a brittle material, comprising a resin, acrylic modified cellulose, an impact modifier, an inorganic filler, a thermoplastic elastomer and a curing agent; the contents of the acrylic modified cellulose, the impact modifier, the inorganic filler, the thermoplastic elastomer and the curing agent are 1-12wt%, 1-20wt%, 10-35wt%, 0.5-2wt% and 2-7wt% of the resin, respectively.
[0004] Based on the composition provided by the present invention, which uses acrylic acid-modified cellulose and has a suitable ratio of thermoplastic elastomer and inorganic filler, the anti-counterfeiting fragile label formed has suitable initial directional tear resistance and fragility. The certain initial directional tear resistance enables it to be tear-resistant during production, transportation or normal use to avoid damage, and its fragility means that once the label is removed, it will quickly decompose into small fragments and cannot be used again in its entirety, thereby preventing it from being illegally stolen or replaced without authorization, thereby achieving the purpose of anti-counterfeiting.
[0005] Acrylic acid-modified cellulose can form a network structure and provide a large amount of gel matrix, which can increase the hardness of fragile materials and work together with thermoplastic elastomers to improve the rigidity and tear resistance of fragile materials. In addition, acrylic acid-modified cellulose can also improve the appearance smoothness and glossiness of fragile materials; from a production perspective, acrylic acid-modified cellulose does not produce bubbles and brush marks when preparing fragile materials, solving the problem of bubbles and brush marks that unmodified cellulose is prone to.
[0006] In some embodiments, the method for preparing the acrylic acid-modified cellulose comprises: Activate the hydroxyl groups in cellulose; A mixed reaction system containing acrylic monomers, activated cellulose and an initiator is reacted at a temperature of 60-70° C., and the acrylic monomers are polymerized and combined with the cellulose through chemical bonds, thereby forming the acrylic acid-modified cellulose.
[0007] In some embodiments, the mass ratio of the acrylic monomer to cellulose is 2:1-5:1.
[0008] In some embodiments, the acrylic monomer includes acrylic acid and / or methacrylic acid, but is not limited thereto.
[0009] In some embodiments, the cellulose includes one or more combinations of natural plant cellulose, semisynthetic cellulose or regenerated cellulose, such as microcrystalline cellulose, lignin, wood fiber, cotton fiber, hemp fiber, cellulose acetate, nitrocellulose, ethyl cellulose, viscose fiber, Lyocell fiber, hydroxyethyl cellulose, carboxymethyl cellulose, but not limited thereto.
[0010] In some embodiments, the cellulose is a powder with a particle size of 10-50 μm.
[0011] In some embodiments, the amount of the initiator is 5-9 wt % of the acrylic monomer.
[0012] In some embodiments, the initiator includes ammonium persulfate, but is not limited thereto.
[0013] In some embodiments, alkali solution is used to activate the hydroxyl groups in cellulose. For example, cellulose is placed in an alkali solution with a concentration of 0.5-2.0 mol / L, wherein the mass ratio of cellulose to the alkali solution is 1:10, and stirred at room temperature for more than 2 hours to activate the hydroxyl groups on the surface of cellulose, thereby increasing the affinity of cellulose for acrylic monomers.
[0014] In some embodiments, the resin includes one or a combination of emulsified polyurethane prepolymer resin, BMI resin, polyarylethylene resin, and silicone resin.
[0015] In some preferred embodiments, the resin includes an emulsified polyurethane prepolymer resin.
[0016] In some embodiments, the method for preparing the emulsified polyurethane prepolymer resin comprises: The second mixed reaction system containing polyether diol and diisocyanate is first reacted at 40-70°C for 1-2 hours, and then heated to 80-85°C for 2-2.5 hours to obtain an intermediate product; The third mixed reaction system containing the intermediate product and the chain extender is reacted at 50-70° C. for 1-2 hours, and then at 80-85° C. for 2-2.5 hours to obtain a polyurethane prepolymer resin; The polyurethane prepolymer resin, emulsifier, liquid tackifying resin and water are mixed and emulsified to form the emulsified polyurethane prepolymer resin; The emulsified polyurethane prepolymer resin prepared by the above method can make the anti-counterfeiting fragile label have good high temperature resistance; and the resin can also provide good stiffness for fragile materials, so that the fragility of the anti-counterfeiting fragile label is easier to reflect, because if the material is soft, the label is not easy to tear off, and it is not easy to achieve the anti-counterfeiting purpose of "fragile".
[0017] In some embodiments, the mass ratio of the polyether diol, diisocyanate, and chain extender is (200-300): (250-190): (4-10).
[0018] In some embodiments, the polyether glycol includes PPG1000 and / or PPG2000, but is not limited thereto.
[0019] In some embodiments, the diisocyanate includes toluene diisocyanate and / or diphenylmethane diisocyanate, but is not limited thereto.
[0020] In some embodiments, the chain extender includes one or a combination of ethylene glycol, dimethylol propionic acid, and dimethylol butyric acid, but is not limited thereto.
[0021] In some embodiments, the emulsifier includes one or a combination of more of OP-10, SDBS, and OT-75, but is not limited thereto.
[0022] In some embodiments, the liquid tackifying resin includes one or a combination of liquid petroleum resin, liquid rosin resin, and liquid terpene resin, but is not limited thereto.
[0023] In some embodiments, the NCO content in the polyurethane prepolymer resin is 8wt%~12wt%.
[0024] In some embodiments, the mass ratio of the polyurethane prepolymer resin to the liquid tackifying resin is 1-3:1, the mass ratio of the polyurethane prepolymer resin to water is 20-60:1, and the mass of the emulsifier is 1-10wt% of the total mass of the mixture.
[0025] In some embodiments, the impact modifier includes one or more of chlorinated polyethylene, acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer, polyolefin elastomer, but is not limited thereto. The impact modifier can help improve the elongation at break of the anti-counterfeiting fragile label.
[0026] In some embodiments, the inorganic filler includes one or more of titanium dioxide, carbon black, and silicon dioxide, but is not limited thereto. The inorganic filler preferably includes titanium dioxide, and the titanium dioxide of gold crystal stone can improve the UV resistance of the anti-counterfeiting fragile label.
[0027] The ratio of the inorganic filler and the thermoplastic elastomer in the composition synergistically affects the fragility and tensile properties of the anti-counterfeiting fragile label. Under the conditions of 10-35wt% of the inorganic filler and 0.5-2wt% of the thermoplastic elastomer, the label can have both suitable fragility and tensile properties.
[0028] In some embodiments, the thermoplastic elastomer includes one or more of acrylic elastomer, diene elastomer, olefin elastomer, amide elastomer, ester elastomer, polyurethane elastomer, vinyl chloride elastomer, and styrene elastomer, but is not limited thereto.
[0029] In some preferred embodiments, the thermoplastic elastomer includes an acrylic elastomer. The acrylic elastomer can not only cooperate with acrylic modified cellulose and inorganic fillers to obtain good initial directional tear resistance, but also can produce a composition with good light transmittance and better fluidity, and the weather resistance and anti-yellowing performance of the produced fragile material are also better.
[0030] In some embodiments, the curing agent includes one or a combination of isocyanate curing agents and aromatic amine curing agents, but is not limited thereto.
[0031] In some embodiments, the composition further comprises 1-8 wt% of an antioxidant. The antioxidant may be any one or a combination of the existing antioxidants, which are not particularly limited in the present invention, such as alkylphenols, butylated toluene, aromatic amines, phenyl-B-resistant amines, alkylene bisphenols, alkenyl bisphenols, alkylphenol sulfides, phenyl salicylate, phenols, phenols, etc.
[0032] In some embodiments, the composition further comprises 0.5-12 wt% of an anti-UV stabilizer. The anti-UV stabilizer may be any one or a combination of existing ones, which is not particularly limited in the present invention, such as benzoic acid, benzophenone, benzotriazole, hindered amine (such as UV-531, UV-944), hindered amine (such as XH-622LD), etc.
[0033] A second object of the present invention is to provide a brittle material, which is formed by solidifying the composition for preparing the brittle material.
[0034] The third object of the present invention is to provide the composition for preparing fragile materials or the use of the fragile materials in preparing anti-counterfeiting fragile labels.
[0035] The fourth object of the present invention is to provide an anti-counterfeiting fragile label, which includes a release film layer, an adhesive layer, a fragile layer, an isolation layer and a laser printing layer stacked in sequence; wherein the fragile layer includes the fragile material.
[0036] Based on the composition provided by the present invention, which uses acrylic acid-modified cellulose and has a suitable ratio of thermoplastic elastomer and inorganic filler, the anti-counterfeiting fragile label has both suitable initial directional tear resistance and fragility. The certain initial directional tear resistance enables it to have tear resistance during production, transportation or normal use to avoid damage, and its fragility makes the label once removed, it will quickly decompose into small fragments and cannot be used again in its entirety, thereby avoiding its illegal theft and unauthorized replacement, and achieving the purpose of anti-counterfeiting. In addition, acrylic acid-modified cellulose can also increase the adhesion between the fragile layer and the isolation layer, so that the bearing capacity of the fragile material is further improved. The anti-counterfeiting fragile label provided by the present invention also has excellent weather resistance, high temperature anti-yellowing and UV stability.
[0037] The isolation layer in the anti-counterfeiting fragile label is used to isolate the fragile layer from the laser printing layer to prevent the laser printing ink contained in the laser printing layer from affecting the fragile substrate layer. In some embodiments, the isolation layer is a UV type isolation layer. The thickness of the isolation layer is 1-2 μm.
[0038] In some embodiments, the thickness of the fragile layer is 75-100 μm. Based on the characteristics of the composition provided by the present invention, if the thickness of the fragile layer is too low, it will not provide the necessary support and stiffness. If the fragile layer is too thick, it will lead to an increase in production costs. Considering comprehensively, the thickness of the fragile layer is preferably 75-100 μm.
[0039] The laser printing layer in the anti-counterfeiting fragile label is used for laser printing to form characteristic information, such as patterns, texts, etc. In some embodiments, the material of the laser printing layer includes UV ink. The thickness of the laser printing layer is 2-10 μm.
[0040] In some embodiments, the thickness of the adhesive layer is 5-10 μm.
[0041] In some preferred embodiments, the adhesive layer contains 1-13wt% of a fluorescent indicator. The addition of the fluorescent indicator can leave a fluorescent mark on the target object after the label is removed, thereby further increasing the anti-counterfeiting effect. The adhesive used in the adhesive layer can be any existing adhesive, and the present invention is not particularly limited to this. For example, different pressure-sensitive adhesive formulas can be selected and designed according to different adhesives.
[0042] In some preferred embodiments, the hardness of the adhesive is 50-90 shore A. The adhesive layer within this hardness range is not easy to interfere with the breakage of the label. If the hardness of the adhesive layer is low, its own tensile properties will affect the fragility of the fragile layer.
[0043] In some embodiments, the anti-counterfeiting fragile label further includes a protective layer, which is located on the side of the laser printing layer away from the isolation layer. The protective layer is used to provide the label with protection such as wear resistance and waterproofness, and can be formed of any existing material with waterproof and wear resistance properties, and the present invention does not specifically limit this.
[0044] In some embodiments, the thickness of the protective layer is 1-2 μm.
[0045] The method for preparing the anti-counterfeiting fragile label comprises: providing a release film, coating the composition on the release film, and curing to form the fragile layer; then sequentially forming an isolation layer, a laser printing layer, and optionally a protective layer on the fragile layer to obtain the anti-counterfeiting fragile label. The machine speed for coating the composition on the release film can be 2-10 m / min. The anti-counterfeiting fragile label can be mass-produced by the above method, and due to its good initial tear resistance, no loss of the label will be caused during the production process.
[0046] Compared with the prior art, the present invention has at least the following technical effects: the present invention provides a composition for preparing fragile materials, and by adopting acrylic modified cellulose, thermoplastic elastomer and inorganic filler and applying appropriate proportions, the anti-counterfeiting fragile label formed by the fragile material has good initial tear resistance, elongation at break and fragility, so that it is not easily damaged during normal use such as production, transportation, and bonding to target objects, and it will quickly decompose into small fragments when torn off and cannot be used again in its entirety, thereby achieving an anti-counterfeiting effect; at the same time, the anti-counterfeiting fragile label provided by the present invention also has excellent weather resistance, high temperature resistance, high temperature yellowing resistance and UV stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1 Schematic diagram of the structure of the anti-counterfeiting fragile label prepared in Example 1 of the present invention; 1-protective layer, 2-laser printing layer, 3-isolation layer, 4-fragile layer, 5-adhesive layer / release film layer. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0050] In addition, unless otherwise specified, the various raw materials used in the following examples can be purchased from the market and other channels, and the various production and testing equipment used are also equipment known in the art.
[0051] Example 1 Example 1 provides a composition and uses the composition to prepare an anti-counterfeit fragile label, as follows: (1) Preparation of acrylic acid-modified cellulose The microcrystalline cellulose powder was placed in a flask containing an appropriate amount of NaOH solution, the concentration of the NaOH solution was 1 mol / L, and the mass ratio of cellulose to the NaOH solution was 1:10; the mixture was stirred at room temperature for 2 hours to activate the hydroxyl groups on the surface of the cellulose and increase its affinity for the acrylic acid monomer; the cellulose powder was then washed with deionized water until it was neutral to remove the unreacted NaOH; The activated microcrystalline cellulose powder is added to a reaction system containing acrylic acid monomer, APS initiator and deionized water, wherein the mass ratio of acrylic acid monomer to cellulose is 2:1, and the amount of APS initiator is 5% of the mass of acrylic acid monomer; under nitrogen protection, the reaction system is heated to 60°C, and stirred at this temperature for 4 hours to obtain acrylic acid-modified cellulose; after the reaction is completed, the product is washed with deionized water for multiple times to remove unreacted acrylic acid monomer, APS initiator and other impurities, and then the product is placed in a vacuum drying oven and dried at 60°C for 24 hours to remove residual moisture.
[0052] (2) Preparation of high temperature resistant resin 200g of polyether diol (GE-210) and 250g of liquefied diphenylmethane diisocyanate (CDMDI-100L) were poured into a three-necked flask with a stirring and temperature measuring device, heated to 40°C at a heating rate of 5°C / min, the temperature in the reaction flask was controlled to be 40°C by cooling the liquid, reacted for 1 hour, and the stirring speed was controlled to be 100 rpm; then the temperature was raised to 80°C at a heating rate of 5°C / min, reacted at a speed of 100 rpm for 2 hours, then cooled to 60°C, 10g of dihydroxymethylpropionic acid was added thereto, the temperature was controlled to be 50°C, reacted at a speed of 100 rpm for 1 hour, then heated to 80°C at a heating rate of 5°C / min, reacted at a speed of 100 rpm for 2 hours, and cooled to below 40°C to prepare 460g of a transparent and viscous polyurethane prepolymer resin.
[0053] The prepared polyurethane prepolymer is mixed with emulsifier OP-10, liquid terpene resin and water, wherein the mass ratio of the polyurethane prepolymer to the liquid terpene resin is 3:1, the mass ratio of the polyurethane prepolymer to the water is 60:1, and the content of the emulsifier OP-10 is 5wt%, and the mixture is fully emulsified to form an emulsified polyurethane prepolymer resin.
[0054] (3) Preparing a composition: adding the acrylic modified cellulose, impact modifier (chlorinated polyethylene), inorganic filler titanium dioxide, acrylic elastomer and curing agent HDI trimer prepared above to the emulsified polyurethane prepolymer resin prepared above; wherein the contents of acrylic modified cellulose, impact modifier chlorinated polyethylene, titanium dioxide, acrylic elastomer and HDI trimer are 6wt%, 10wt%, 20wt%, 1wt% and 5wt% of the total mass of the emulsified polyurethane prepolymer resin, respectively.
[0055] (4) Preparation of anti-counterfeiting fragile labels The prepared composition is coated on a release film by a scraper at a machine speed of 10 m / min, and the thickness of the dry glue is adjusted according to the scraper gap and the speed ratio to form a fragile layer with a thickness of 100 μm; then a UV-type isolation layer (made of UV-type varnish) with a thickness of 1 μm is coated on the fragile layer; a laser printing layer with a thickness of 2 μm is formed on the UV-type isolation layer by using UV ink; then a UV-type varnish protective layer with a thickness of 1 μm is formed on the UV-type isolation layer by using varnish; then a bonding layer with a thickness of 5 μm is formed on the side of the fragile layer away from the isolation layer and a release film layer is attached to obtain an anti-counterfeiting fragile label. Figure 1It is a schematic diagram of the structure of an anti-counterfeiting fragile label, including an adhesive layer / release film layer 5 (representing the laminated release film layer and adhesive layer, the adhesive layer is located on the side close to the fragile layer 4), a fragile layer 4, an isolation layer 3, a laser printing layer 2 and a protective layer 1. Among them, the adhesive layer is a pressure-sensitive adhesive with 13wt% fluorescent indicator, so that the label can leave a fluorescent mark on the target object when it is removed, further increasing the anti-counterfeiting effect.
[0056] Example 2 Example 2 is basically the same as Example 1, except that, in the composition of Example 2, the contents of acrylic modified cellulose, impact modifier chlorinated polyethylene, titanium dioxide, acrylic elastomer and HDI trimer are 1wt%, 20wt%, 35wt%, 0.5wt% and 2wt% of the mass of the emulsion polyurethane prepolymer resin, respectively; and the composition also includes 1wt% of the antioxidant phenyl salicylate and 2wt% of the anti-UV stabilizer UV-531, based on the mass of the emulsion polyurethane prepolymer resin.
[0057] The rest is implemented in the same manner as in Example 1 and will not be described again.
[0058] Example 3 Example 3 is basically the same as Example 1, except that the composition of Example 2 is as follows: the contents of acrylic modified cellulose, impact modifier chlorinated polyethylene, titanium dioxide, acrylic elastomer and HDI trimer are 12wt%, 1wt%, 10wt%, 2wt% and 7wt% of the mass of the emulsion polyurethane prepolymer resin, respectively; and also includes 8wt% of the antioxidant phenyl salicylate and 12wt% of the anti-UV stabilizer UV-531, based on the mass of the emulsion polyurethane prepolymer resin.
[0059] The rest is implemented in the same manner as in Example 1 and will not be described again.
[0060] Example 4 The only difference between Example 4 and Example 1 is that the thickness of each layer in the anti-counterfeiting fragile label prepared in Example 5 is different, namely: adhesive layer 10μm, fragile layer 70μm, UV isolation layer 2μm, laser printing layer 10μm and UV varnish protection layer 2μm.
[0061] The rest is implemented in the same manner as in Example 1 and will not be described again.
[0062] Example 5 The only difference between Example 5 and Example 1 is that the acrylic elastomer used in Example 1 is replaced by an amide elastomer.
[0063] The rest is implemented in the same manner as in Example 1 and will not be described again.
[0064] Example 6 The only difference between Example 6 and Example 1 is that the acrylic elastomer used in Example 1 is replaced by a styrene elastomer.
[0065] By comparing Example 1, Example 5 and Example 6, it is found that although amide elastomers and styrene elastomers can also obtain fragile materials with certain initial tear resistance, the weather resistance and yellowing resistance of the obtained fragile materials are reduced compared with acrylic elastomers. The present invention also tests ester elastomers, urethane elastomers, and vinyl chloride elastomers. Considering the comprehensive initial directional tear resistance, fragility, weather resistance and yellowing resistance, acrylic elastomer has better comprehensive performance.
[0066] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that microcrystalline cellulose not modified with acrylic acid is used in Comparative Example 1. The rest is implemented in the same way as Example 1, which will not be described in detail here.
[0067] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the composition of Comparative Example 2 does not contain acrylic elastomer. The rest is the same as Example 1 and will not be repeated here.
[0068] Comparative Example 1 and Comparative Example 2 show that when the composition does not contain thermoplastic elastomer or its content is too low, the fragile material will be too weak in flexibility and particularly easy to be damaged, making it difficult to operate during production and processing, and the label will also be easily damaged during normal use.
[0069] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the content of the acrylic elastomer in the composition of Comparative Example 3 is 20 wt % of the resin content). The rest is implemented in the same way as Example 1, which will not be repeated here.
[0070] It is found that when the content of thermoplastic elastomer in the composition is too high, it will lead to greater flexibility of the fragile material, which will affect its anti-counterfeiting performance.
[0071] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the thickness of the fragile layer in the anti-counterfeiting fragile label of Comparative Example 4 is 20 μm. The rest is implemented in the same way as Example 1 and will not be described again.
[0072] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the thickness of the fragile layer in the anti-counterfeiting fragile label of Comparative Example 5 is 150 μm. The rest is implemented in the same way as Example 1 and will not be described again.
[0073] The relevant properties of the fragile anti-counterfeiting labels prepared in the above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0074] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is that the emulsified polyurethane prepolymer resin in Example 1 is replaced by a cyanate ester resin.
[0075] The rest is implemented in the same manner as in Example 1 and will not be described again.
[0076] In addition, the present invention also tests other high temperature resistant resins, including BMI resin, polyarylethylene resin, and silicone resin, and the high temperature resistance effect of the anti-counterfeiting fragile label is equivalent to that of Example 4. However, compared with Example 1, it is found that the emulsified polyurethane prepolymer resin not only has good high temperature resistance, but also can provide good stiffness for fragile materials, so that it shows better anti-counterfeiting fragility when it is torn off, so the emulsified polyurethane prepolymer resin has better comprehensive performance.
[0077] Table 1 Relevant properties of fragile anti-counterfeiting labels prepared in the examples and comparative examples of the present invention
[0078] In Table 1, in the aging resistance, initial tear strength, elongation at break, abrasion resistance, liquid resistance and fragility, "√" represents that the test results according to the following standards and test methods are in compliance, and "×" represents that the test results according to the following standards and test methods are not in compliance.
[0079] The detection methods of the relevant properties in Table 1 are as follows: 1. Yellowing and cracking: Place the label in a high temperature environment of 150°C for 1600 hours, then take it out and place it in a standard environment for 1 hour to observe whether yellowing and cracking occur.
[0080] 2. Xenon lamp aging test: Aging test is carried out with a xenon lamp with a blackboard temperature of 65℃±3℃, in a cycle of 102 min of illumination and 18 min of water spraying.
[0081] 3. Initial tear strength: tested according to ASTM D1004 method.
[0082] 4. Wear resistance test: The wear resistance test is carried out for 200 cycles under the conditions of 500g load and 30r / min speed. The labels should be intact in appearance, without any adhesive separation or damage, and there should be no obvious change in surface color compared with the samples before the test, then they are qualified.
[0083] 5. Liquid resistance: Tested according to GB / T 25978-2018.
[0084] 6. Thermal cycle test: According to GB / T 25978-2018, the label is placed at 150℃±2℃ for 30 minutes. If there is no obvious change in the color of the label surface and the information on the label is clear and easy to identify, it is qualified.
[0085] 7. Heat aging test: GB / T 25978-2018 "Road Vehicle Signs and Labels" (or Label Technical Conditions), page 12, test method 5.3.7c) Place the test under 150℃±2℃ for 1600h, then place it under standard environment for 1h and inspect visually.
[0086] 8. High-pressure cleaning resistance test: Place the label under standard environmental conditions for 24 hours, and use a high-pressure water gun with a pressure of 8.50MPa±0.34MPa and water temperature at room temperature to spray at a 45° angle at a distance of 20cm from the label for 5 seconds. The appearance is intact, there is no color difference, and the information is clearly visible.
[0087] 9. Elongation at break: Tested according to ASTM D3759 method.
[0088] 10. Tamper-proof performance test: GB / T 25978-2018 "Road Vehicle Signs and Labels" (or Label Technical Conditions) Page 14 Test Method 5.3.12 Prepare a label with a width of 40mm ± 1mm and a length of 60mm ± 1mm (the label edge should be smooth and without cuts, except for the pre-made cuts given by the design), paste the label on the test board, and roll it back and forth on its surface with a 2kg, 50mm wide roller at a speed of 300mm / min to ensure that the label is completely pasted, and place it in a standard environment for 14 days. Manually peel the label from the test board from one end of the label (at a 45° angle) with the help of a utility knife at a speed of about 30mm / min.
[0089] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0090] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0091] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.
Claims
1. A composition for preparing a brittle material, characterized in that: The invention comprises resin, acrylic acid modified cellulose, impact modifier, inorganic filler, thermoplastic elastomer and curing agent; the contents of acrylic acid modified cellulose, impact modifier, inorganic filler, thermoplastic elastomer and curing agent are 1-12wt%, 1-20wt%, 10-35wt%, 0.5-2wt% and 2-7wt% of the resin respectively.
2. The composition according to claim 1, characterized in that The preparation method of the acrylic acid modified cellulose comprises: Activate the hydroxyl groups in cellulose; The first mixed reaction system containing acrylic monomer, activated cellulose and initiator is reacted at a temperature of 60-70° C., and the acrylic monomer is polymerized and combined with the cellulose through chemical bonds to form the acrylic modified cellulose.
3. The composition according to claim 2, characterized in that: The mass ratio of the acrylic acid monomer to cellulose is 2:1 to 5:1; and / or, the acrylic monomer comprises acrylic acid and / or methacrylic acid; And / or, the cellulose includes one or more of natural plant cellulose, semisynthetic cellulose or regenerated cellulose; preferably, the cellulose includes one or more of microcrystalline cellulose, lignin, wood fiber, cotton fiber, hemp fiber, cellulose acetate, nitrocellulose, ethyl cellulose, viscose fiber, Lyocell fiber, hydroxyethyl cellulose, carboxymethyl cellulose; And / or, the cellulose is a powder with a particle size of 10-50 μm; and / or, the amount of the initiator is 5-9wt% of the acrylic monomer; and / or, the initiator comprises ammonium persulfate; And / or, hydroxyl groups in cellulose are activated by using alkaline solution.
4. The composition according to claim 1, characterized in that: The resin includes one or a combination of emulsified polyurethane prepolymer resin, BMI resin, polyarylethylene resin, and silicone resin. Preferably, the resin includes emulsified polyurethane prepolymer resin.
5. The composition according to claim 4, characterized in that: The preparation method of the emulsified polyurethane prepolymer resin comprises: The second mixed reaction system containing polyether diol and diisocyanate is first reacted at 40-70°C for 1-2 hours, and then heated to 80-85°C for 2-2.5 hours to obtain an intermediate product; The third mixed reaction system containing the intermediate product and the chain extender is reacted at 50-70° C. for 1-2 hours, and then at 80-85° C. for 2-2.5 hours to obtain a polyurethane prepolymer resin; The polyurethane prepolymer resin, the emulsifier, the liquid tackifying resin and water are mixed to form a mixture, and then emulsified to form the emulsified polyurethane prepolymer resin; Preferably, the mass ratio of the polyether diol, diisocyanate and chain extender is (200-300): (250-190): (4-10); Preferably, the polyether diol includes PPG1000 and / or PPG2000; the diisocyanate includes toluene diisocyanate and / or diphenylmethane diisocyanate; the chain extender includes one or more of ethylene glycol, dimethylol propionic acid, and dimethylol butyric acid; the emulsifier includes one or more of OP-10, SDBS, and OT-75; the liquid tackifying resin includes one or more of liquid petroleum resin, liquid rosin resin, and liquid terpene resin; Preferably, the NCO content in the polyurethane prepolymer resin is 8wt%~12wt%; Preferably, the mass ratio of the polyurethane prepolymer resin to the liquid tackifying resin is 1-3:1, the mass ratio of the polyurethane prepolymer resin to water is 20-60:1, and the mass of the emulsifier is 1-10wt% of the total mass of the mixture.
6. The composition according to claim 1, characterized in that: The impact modifier includes one or a combination of chlorinated polyethylene, acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer, and polyolefin elastomer; And / or, the inorganic filler includes one or a combination of titanium dioxide, carbon black, and silicon dioxide; And / or, the thermoplastic elastomer includes one or a combination of acrylic elastomer, diene elastomer, olefin elastomer, amide elastomer, ester elastomer, urethane elastomer, vinyl chloride elastomer, and styrene elastomer; And / or, the curing agent includes one or a combination of isocyanate curing agents and aromatic amine curing agents; And / or, the composition further comprises 1 to 8 wt % of an antioxidant; And / or, the composition further comprises 0.5-12 wt % of an anti-UV stabilizer.
7. A fragile material, characterized in that: The brittle material is formed by solidifying the composition for preparing brittle materials according to any one of claims 1 to 6.
8. Use of the composition for preparing fragile materials according to any one of claims 1 to 6 or the fragile material according to claim 7 in preparing anti-counterfeiting fragile labels.
9. An anti-counterfeiting fragile label, characterized in that: It comprises a release film layer, an adhesive layer, a fragile layer, an isolation layer and a laser printing layer which are stacked in sequence; wherein the fragile layer comprises the fragile material according to claim 7.
10. The anti-counterfeiting fragile label according to claim 9, characterized in that: The isolation layer is a UV type isolation layer; And / or, the thickness of the isolation layer is 1-2 μm; and / or, the thickness of the fragile layer is 75-100 μm; And / or, the thickness of the laser printing layer is 2-10 μm; And / or, the thickness of the bonding layer is 5-10 μm; and / or, the bonding layer contains 1-13 wt % of a fluorescent indicator; and / or, the hardness of the bonding layer is 50-90 shore A; And / or, it also includes a protective layer with a thickness of 1-2 μm, and the protective layer is located on a side of the laser printing layer away from the isolation layer.